Peran Pendidikan Pesantren Sebagai Pembentukan Karakter Religius Santri dalam Menghadapi Tantangan di Era Society 5.0 di Pondok Pesantren Al-Wasilah Mardhotillah - Boehari, Anis; Maryam, Siti (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
This research aims to analyze the role of Islamic boarding school education in shaping the religious character of students at the Al-Wasilah Mardhotillah Islamic Boarding School in facing the challenges of the Society 5.0 era. Religious character education is very important, especially in this digital era, where the influence of technology and information can threaten moral values. The research method used is a qualitative method with data collection techniques through observation, interviews and documentation. This research highlights several methods of forming religious character that are applied in Islamic boarding schools, such as habituation, example, advice, supervision, and punishment. The results of the research show that the Al-Wasilah Mardhotillah Islamic Boarding School has succeeded in implementing these methods in forming the religious character of its students. However, challenges such as physical fatigue, lack of variety in learning methods, and limited understanding of religious material are inhibiting factors in the character formation process. For this reason, Islamic boarding schools are expected to make improvements in terms of balancing activity schedules and varying learning methods to make them more interesting and interactive. This research concludes that Islamic boarding school education plays a key role in facing the challenges of the Society 5.0 era, by providing a strong foundation of moral and religious values for students.